Evaluasi Pengendalian Internal dan Sistem Akuntansi atas Penerimaan Kas dan Piutang Premi Asuransi pada PT H - Seoulinda, Nena; Wicaksono, Aries (Bina Nusantara University, 2012)
PT H is an insurance company that only serves a group of life insurance. The purpose of this research is to evaluate the entityâs internal control and accounting system on cash receipt and insurance premium receivables. To conduct the research, the researcher used a method based on Committe of Sponsoring Organization or usually known as COSO. The data were collected from literatures such as textbooks, and other references, such as theories and scientific opinions related to this topic. Apart from the theories, researcher performed interviews, spread questionnaries, and observations to the entity. The internal control and accounting system in PT H has been well organized by the management and in accordance with the standards and the Entityâs policy. But other than that, the researcher found several weakness that should be a concern of management, especially on the Entityâs documentation and the delivery of information. Therefore, the researcher recommends that serial number in documents such as receipt, payment request form, and accounting request form should have been printed; to create a new company policy related to the delivery and receiving of files; and to make a written rules related to the Entityâs code of ethics and rules how to deliver information between sections and subsections.